Live Commerce Performance and Actual Sales Volume: Evidence from Skincare Brands on TikTok Shop Indonesia - Ziaul Maula; Rahmat Maulidan; Farathika Putri Utami (FEBI IAIN Langsa, 2026)
Live commerce has become a strategic digital selling channel for skincare brands because it combines product visualization, real-time interaction, and direct transaction. However, prior live commerce studies still rely heavily on survey-based purchase intention, leaving limited evidence on whether platform-level live streaming metrics are associated with actual sales outcomes. This study examines the association between live commerce performance indicators and actual sales volume using secondary FastMoss data from 3,000 TikTok Shop live streaming sessions across ten leading skincare brands in Indonesia. The predictors include live viewers, live duration, product assortment, and creator followers, while brand fixed effects are used to control unobserved cross-brand heterogeneity. The data are analyzed using multiple linear regression with HC3 robust standard errors. The model explains 82.5% of sales volume variation. Live viewers, product assortment, live duration, and creator followers are positively and significantly associated with actual sales volume. The effect-size comparison shows that active viewers and product assortment have much stronger associations than creator followers. The findings suggest that live commerce conversion is more closely related to active audience presence and product relevance than to passive reach, while causal claims remain limited by the observational platform-data design.